2019
DOI: 10.1111/cid.12730
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐year prospective case series on volumetric changes, PROMs, and clinical outcomes following sinus floor elevation using deproteinized bovine bone mineral as filling material

Abstract: Background A sinus floor augmentation may be indicated when a lack of hard tissue impedes implant placement. Although clinically successful, evidence supporting the long‐term three‐dimensional stability of the grafted volume is scarce. Second, evidence on the patient's acceptance of this type of treatment is limited. Purpose First is to evaluate the changes in graft volume after lateral wall sinus lifting based on superimposed cone beam computed tomography (CBCT) images and then to assess patient‐reported outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 59 publications
(165 reference statements)
2
33
0
Order By: Relevance
“…Apart from the three fully synthetic calcium phosphate bone substitutes used in the present study, xenografts, such as demineralized bovine bone mineral (DBBM), have been also widely used in MSFE procedures [43][44][45][46][47]. Clinical, radiological, and histomorphometrical studies on DBBM confirmed predictable outcomes after MSFE, meaning good quality and volume of regenerated tissue [17].…”
Section: Discussionmentioning
confidence: 63%
“…Apart from the three fully synthetic calcium phosphate bone substitutes used in the present study, xenografts, such as demineralized bovine bone mineral (DBBM), have been also widely used in MSFE procedures [43][44][45][46][47]. Clinical, radiological, and histomorphometrical studies on DBBM confirmed predictable outcomes after MSFE, meaning good quality and volume of regenerated tissue [17].…”
Section: Discussionmentioning
confidence: 63%
“…Other factors that may have an impact on clinical decision‐making are pain, oedema and haematoma during the early stages of healing. Ad hoc questions with a VAS scoring method that had already been validated in another study (Younes, Cosyn, De Bruyckere, Cleymaet, & Eghbali, ) were used to assess these PROMs. Pain was comparable in both groups, even though patients took more painkillers in the control group (7.10) than in the test group (4.86).…”
Section: Discussionmentioning
confidence: 99%
“…First, PROMs are difficult to assess and compare among studies given the lack of standardization in the literature. However, we used questions with a VAS scoring method that had already been validated in earlier research (Younes et al, ) and patients scored in the absence of the surgeon to reduce bias. Second, ample variables were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The last of the parameters that this study proposed to evaluate was that related to the influence of oral health, in this case after an MSA procedure such, on the quality of life. We decided to do it with a questionnaire, adopted by many other studies, handed to the patient at a specific time point, but with questions that related to the entire previous period 39‐41 . The total scores of the OHIP‐14 for the three groups were very low, showing that, despite its invasiveness, an MSA procedure does not have a negative impact on the quality of life of our patients.…”
Section: Discussionmentioning
confidence: 99%